2000
DOI: 10.1007/s003300000461
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal torsion: MR imaging findings of viable ovary

Abstract: We report a case of torsed ovarian cystic tumor, in which contrast-enhanced high-resolution MR images accurately contributed to the diagnosis of torsion despite the lack of symptoms and to the preoperative evaluation of viability of the edematous ovary. Accurate preoperative assessment by MR images and prompt conservative surgical approach succeeded in salvaging the involved ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 4 publications
(11 reference statements)
2
12
0
Order By: Relevance
“…3,11,12 Furthermore, due to passive congestion, T 1 -weighted images depicted a torsed ovary without hemorrhagic infarction as hyperintense. 13 Methemoglobin generated during the subacute phase of hemorrhage causes shortening of T 1 relaxation time that results in hyperintensity on T 1 -weighted images. On the other hand, acute hemorrhage containing oxy-or deoxyhemoglobin is depicted as iso-or hypointense on T 1 -weighted images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,11,12 Furthermore, due to passive congestion, T 1 -weighted images depicted a torsed ovary without hemorrhagic infarction as hyperintense. 13 Methemoglobin generated during the subacute phase of hemorrhage causes shortening of T 1 relaxation time that results in hyperintensity on T 1 -weighted images. On the other hand, acute hemorrhage containing oxy-or deoxyhemoglobin is depicted as iso-or hypointense on T 1 -weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperintensity of enlarged ovarian stroma on T 2 -weighted images may indicate an edematous condition in viable torsed ovaries, 13,14 whereas hypointensity may indicate hemorrhagic infarction. 3,11,12 In our series, we observed no significant difference in signal intensity ratios on T 2 -weighted images between patients with and without hemorrhagic infarction, probably because signal intensity on T 2 -weighted images varies during the course of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages, a torsed ovary may be swollen and contain multiple follicles separated by edematous stroma [2]. Hyperintense signal of enlarged ovarian stroma on T2-weighted images probably related to edema can be useful findings in viable torsions [18,19]. When hemorrhagic necrosis occurs, the lesion may exhibit high intensity on T1-weighted images [17,20].…”
Section: Solid/solid and Cystic Lesionsmentioning
confidence: 96%
“…When hemorrhagic necrosis occurs, the lesion may exhibit high intensity on T1-weighted images [17,20]. Identification of the enhancement on postcontrast MR images is an important finding for suggesting the viable tissues in the affected ovary [19]. Lack of enhancement in Fig.…”
Section: Solid/solid and Cystic Lesionsmentioning
confidence: 97%
“…The development of threedimensional sonography may enhance the diagnostic potential of ultrasound [13]. It has also been suggested that magnetic resonance imaging (MRI) has a role in assessing ovarian viability in cases of torsion [14,15].…”
Section: Introductionmentioning
confidence: 99%